Modelling buyer-seller relationships in agribusiness in South East Asia - Batt, Peter (University of Bath, 2000)
A model of buyer-seller relationships is developed to examine the nature of the long-term relationships between Filipino potato farmers and their seed suppliers. Relational satisfaction is derived from the seed supplier's offer quality (seed quality, delivery intent and competitive price), relationship specific investments (adaptions, communication, education and training and reciprocal buying) and a reduction in uncertainty in the seed supply market. However, rather than satisfaction leading to trust, satisfaction has a more direct impact on a potato farmer's desire to maintain a long-term relationship. Nevertheless, in the absence of a formal seed certification system and the nature of the long-term credit arrangements that often exist between farmers and seed suppliers, including reciprocal purchasing arrangements, trust remains a key relationship building variable. Fortuitously, seed suppliers have an opportunity to build trust with potato farmers through making relationship specific investments.